Ultrasonographic Gallbladder Wall Thickness as a Pathophysiological Predictor of Surgical Outcome in Laparoscopic Cholecystectomy: A Prospective Study - Hasanain Mazyed Shamkh; Alaa Jamel Hasin (Journal of Biomedicine and Biochemistry, 2026)
Background: Laparoscopic cholecystectomy (LC) is the gold standard treatment for symptomatic gallstone disease. Gallbladder wall thickness (GBWT) is a well-established pathophysiological marker reflecting the degree of mural inflammation and fibrosis, and is an important preoperative predictor of surgical difficulty. Thickened gallbladder walls are frequently associated with higher rates of intraoperative complications and prolonged hospital stays. Objectives: To assess the relationship between preoperative ultrasonographic GBWT and the pathophysiological and clinical challenges encountered during laparoscopic cholecystectomy. Patients and Methods: A prospective study conducted on 144 patients who underwent LC at the Surgical Department of Al-Hussain Teaching Hospital and Al-Nassiriya Teaching Hospital, Nasiriyah, Iraq, from January 2023 to July 2024. GBWT was classified by ultrasonography as normal, mild, moderate, or severe. LC difficulty was assessed based on operative time, intraoperative complications, and the ability to achieve the critical view of safety (CVS). Results: LC was classified as easy in 58.33% and difficult in 41.67% of cases. Difficult LC was significantly associated with male sex (21.67% vs. 3.57%, p=0.001), higher BMI (30.29±3.08 vs. 28.71±3.95, p=0.011), elevated WBC count (p=0.001), pericholecystic fluid (35% vs. 7.14%, p<0.001), and moderate/severe GBWT (p<0.001). Moderate/severe GBWT was present in 18% of cases and was significantly associated with older age (48.19±13.36 vs. 41.62±11.45 years, p=0.011), male sex (p=0.032), hypertension (p=0.002), leukocytosis (p=0.016), pericholecystic fluid (p<0.001), prolonged operative time (p<0.001), adhesions (p<0.001), hemorrhage (p=0.045), and postoperative collection (p=0.010). Conclusions: GBWT is a significant preoperative pathophysiological predictor of LC difficulty. Moderate to severe GBWT is associated with higher rates of intraoperative and postoperative complications. Preoperative identification of GBWT by ultrasonography enables better patient counselling and surgical planning.